2015
DOI: 10.1016/j.dsr2.2014.07.007
|View full text |Cite
|
Sign up to set email alerts
|

230Th and 231Pa on GEOTRACES GA03, the U.S. GEOTRACES North Atlantic transect, and implications for modern and paleoceanographic chemical fluxes

Abstract: 29The long-lived uranium decay products 230

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
114
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 90 publications
(119 citation statements)
references
References 103 publications
5
114
0
Order By: Relevance
“…Dissolved 230 Th is removed from the ocean by reversible scavenging to settling particles [63] with a residence time that is sufficiently short (20-40 years in the deep sea) that the tracer experiences relatively little net lateral redistribution between its production in the water column and its burial in the underlying sediments. One modelling study concluded that the removal flux of 230 Th to the sediments is within ±30% of its production rate in the overlying water column throughout approximately 70% of the ocean [64], a finding subsequently shown to apply in our study area [65]. Consequently, the short residence time of dissolved Th allows its mass budget to be applied in a one-dimensional framework with relatively small uncertainty.…”
Section: (A) Aerosol Depositionmentioning
confidence: 87%
See 4 more Smart Citations
“…Dissolved 230 Th is removed from the ocean by reversible scavenging to settling particles [63] with a residence time that is sufficiently short (20-40 years in the deep sea) that the tracer experiences relatively little net lateral redistribution between its production in the water column and its burial in the underlying sediments. One modelling study concluded that the removal flux of 230 Th to the sediments is within ±30% of its production rate in the overlying water column throughout approximately 70% of the ocean [64], a finding subsequently shown to apply in our study area [65]. Consequently, the short residence time of dissolved Th allows its mass budget to be applied in a one-dimensional framework with relatively small uncertainty.…”
Section: (A) Aerosol Depositionmentioning
confidence: 87%
“…Bioturbation of surface sediments filters the record of sediment accumulation over time scales of centuries (near the continents) to millennia (in the open ocean), so the average fluxes derived from surface sediments include dust supplied by rare large events whose signal in the water column dissipated long ago. Sedimentation on the continental slope and rise may also incorporate episodic input of material that was reworked from sites upslope or on the nearby continental shelf [95], as evidenced by nepheloid layers observed along the African margin [65,68]. Partially offsetting these effects, the preferential scavenging of dissolved 230 Th in the particlerich water column near the coast of Mauritania, combined with lateral mixing, generates a net flux of dissolved 230 Th towards the margin.…”
Section: (D) Fluxes Constrained By Normalization To 230 Thmentioning
confidence: 99%
See 3 more Smart Citations